Lithium iron phosphate polymer battery and preparation method thereof
By using porous carbon-encapsulated lithium iron phosphate positive electrode, lithium tetrafluoroaluminate, polyethylene oxide electrolyte and metal lithium negative electrode in polymer lithium-ion batteries, the problem of lithium dendrites puncture electrolyte is solved, and the battery energy density and safety is improved.
Patent Information
- Application Number
- CN202510204232.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-04
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-01-04
AI Technical Summary
There is a problem of lithium dendrites growing into electrolytes in polymer lithium-ion batteries, which leads to short-circuiting of the battery and low conductivity of the electrolyte, which limits the improvement of its energy density and safety.
Lithium iron phosphate wrapped in porous carbon is used as the positive electrode material, lithium tetrafluoroaluminate and polyethylene oxide are combined as the electrolyte, and lithium metal is used as the negative electrode, and the formation of Al-Li alloy and the formation of SEI film are suppressed.
It effectively solves the problem of lithium dendrites piercing electrolyte growth, improves the energy density and safety of the battery, reduces internal resistance and polarization, and enhances the cycling stability of the battery.
Smart Images

Figure CN119852546A_ABST
Abstract
Description
[0001] This case is a divisional application based on the invention patent with application date of 2024-01-04, application number 202410015389.0, and name “High energy density lithium iron phosphate polymer battery and preparation method thereof” as the parent case. Technical Field
[0002] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium iron phosphate polymer battery and a preparation method thereof. Background Art
[0003] With the continuous development of science and technology, the current society has put forward higher requirements for electrochemical energy storage systems. Due to the liquid electrolyte components and battery structure, it is difficult for traditional lithium-ion batteries to improve the safety and energy density of batteries at the same time, which to a certain extent restricts their further development. Compared with liquid lithium-ion batteries, polymer lithium-ion batteries have the advantages of high thermal stability, strong mechanical strength and chemical stability. It is expected to achieve the matching use of high-energy positive electrodes and metal lithium negative electrodes, so that it can take into account both high energy density and high safety. Therefore, polymer batteries have become a new research direction for electrochemical energy storage devices. However, polymer electrolyte ions have the problems of low conductivity and unstable electrolyte / electrode interface, which hinders their widespread application.
[0004] The electrolyte, negative electrode and positive electrode in polymer batteries need to be improved. The electrolytes in polymer batteries include polyether, polycarbonate, polyurethane and polysiloxane. The most studied electrolyte is polyether type polyethylene oxide (PEO), but it has problems such as low conductivity, small lithium ion migration number, narrow electrochemical window and poor thermodynamic stability. -1 The high theoretical specific capacity, -3.04Vvs. standard hydrogen electrode and low oxidation potential of 0.534g / cm -3 The low volume density of metallic lithium as the negative electrode has a significant effect on improving the energy density of the battery. However, studies have shown that when polymer-based solid electrolytes are matched with lithium negative electrodes to assemble solid-state lithium batteries, the battery has serious lithium deposition between the electrolyte and the lithium negative electrode and lithium dendrite growth during long-term charging and discharging. Lithium iron phosphate (LiFePO4) as the main positive electrode material has become one of the most widely commercialized materials due to its low cost, excellent safety performance, and stable operating voltage platform. However, it has 10 -9 S cm -1 Low conductivity, 10 -3 ~10 -6 cm 2 ·s -1 The low ion diffusion rate limits the development of LiFePO4 in polymer batteries.
[0005] The Chinese invention patent with application number 202310690101.5 provides a method for preparing a polymer interface modified inorganic solid electrolyte, in which the electrolyte improves conductivity by adding oxides, and ceramic sheets are added to prepare a sandwich structure of the electrolyte to inhibit the growth of lithium dendrites. However, this method requires the addition of multiple additives to simultaneously achieve the effect of improving electrolyte conductivity and inhibiting lithium dendrite growth. The process is complicated and requires additional steps, and the formation of SEI (solid electrolyte interface) is not considered.
[0006] The Chinese invention patent with application number 201710874217.9 provides a method for preparing a carbon-coated LiFePO4 / CNTs composite positive electrode material for lithium-ion batteries, in which carbon nanotubes modified with cyclodextrin are added to the positive electrode slurry to improve the conductivity of lithium iron phosphate and provide a channel for lithium ions during the charge and discharge process. However, the preparation process is complicated and requires the use of multiple carbon sources, and the pore size of carbon nanotubes is difficult to control, resulting in unstable product performance. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a lithium iron phosphate polymer battery and a preparation method thereof, wherein the preparation method can solve the problem that lithium dendrites grow and pierce the electrolyte.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a lithium iron phosphate polymer battery, including the step of preparing a positive electrode plate, the method for preparing the positive electrode plate comprising: dissolving lithium iron phosphate and polyvinyl pyrrolidone in ethanol and stirring, and then drying, carbonizing and ammonia etching in sequence to obtain porous carbon-wrapped lithium iron phosphate; using the porous carbon-wrapped lithium iron phosphate as the positive electrode active material to prepare the positive electrode plate; the mass of the polyvinyl pyrrolidone is 2~8% of the mass of the lithium iron phosphate.
[0009] Another technical solution adopted by the present invention is: a lithium iron phosphate polymer battery prepared by the above-mentioned preparation method of the lithium iron phosphate polymer battery.
[0010] The beneficial effect of the present invention is that the lithium iron phosphate polymer battery of the present invention solves the problems of battery short circuit and low electrolyte conductivity caused by lithium dendrite growth piercing the electrolyte through the sequentially stacked porous carbon-wrapped lithium iron phosphate positive electrode, the electrolyte containing lithium tetrafluoroaluminate and polyethylene oxide, and the metal lithium negative electrode plate. Lithium tetrafluoroaluminate and polyethylene oxide are used as electrolytes. When they are in contact with the metal lithium negative electrode plate, lithium tetrafluoroaluminate will continuously react with metal lithium and gradually be lithiated to form an in-situ grown Al-Li alloy. This alloy is a good electronic conductor and can inhibit lithium deposition and the formation of lithium dendrites; at the same time, LiF (lithium fluoride) will also be formed during the reaction process to form a stable SEI film to reduce the formation of lithium dendrites, so that the negative electrode-electrolyte interface of the battery cell can be kept stable at a high current density, thereby improving the energy density. Porous carbon-wrapped lithium iron phosphate is also used as the positive electrode. The carbon coating can improve its conductivity, reduce the internal resistance of the system, effectively reduce the polarization caused by the internal resistance, increase its voltage platform and thus enhance the energy density; the porous structure of carbon can increase the reaction channels of lithium ions and enhance the energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic diagram of the structure after the negative electrode and metal lithium contact reaction according to a specific embodiment of the present invention; Figure 2 Shown is a schematic structural diagram of carbon-wrapped lithium iron phosphate according to Example 2 of the present invention; Figure 3 Shown are the charge and discharge curves of the finished batteries of Example 2 of the present invention and Comparative Examples 1 to 3; Figure 4 Shown is a cycle capacity retention rate curve of the finished batteries of Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0012] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes and the accompanying drawings.
[0013] A lithium iron phosphate polymer battery comprises a positive electrode plate, a diaphragm coated with an electrolyte and a metal lithium negative electrode plate which are stacked in sequence. The positive electrode is lithium iron phosphate wrapped with porous carbon, and the electrolyte comprises lithium tetrafluoroaluminate and polyethylene oxide.
[0014] From the above description, it can be seen that the beneficial effect of the present invention is that: the present invention selects metallic lithium as the negative electrode, which is light in weight and has a high theoretical capacity. When lithium tetrafluoroaluminate and polyethylene oxide are used as electrolytes, when they come into contact with the metallic lithium negative electrode plate, lithium tetrafluoroaluminate will construct a three-dimensional structure with the metallic lithium, and the two will continue to react and gradually be lithiated to form an in-situ grown Al-Li alloy. The Al-Li alloy is a good electronic conductor and can inhibit lithium deposition and the formation of lithium dendrites; at the same time, LiF will also be formed during the reaction to form a stable SEI film (see Figure 1 ) to reduce the formation of lithium dendrites, so that the negative electrode-electrolyte interface of the battery cell remains stable at high current density and the energy density is improved.
[0015] There is an interfacial reaction between lithium tetrafluoroaluminate and lithium iron phosphate in the electrolyte. Under high pressure, the lattice O 2- It will transform into strong oxidizing O 2- 2 and forms aluminum oxide at the interface with lithium tetrafluoroaluminate, resulting in increased interfacial impedance; when the polyethylene oxide in the electrolyte matches the lithium iron phosphate, it is easy to undergo oxidative decomposition. The present invention uses porous carbon-wrapped lithium iron phosphate as the positive electrode, which can effectively avoid interfacial reactions, reduce the internal resistance of the system, reduce the polarization caused by the internal resistance, increase its voltage platform, thereby enhancing the energy density, and reduce the side effects of polyethylene oxide oxidative decomposition caused by the interfacial reaction. The porous structure of carbon can increase the reaction channels of lithium ions and enhance the energy density. The above-mentioned positive electrode plates of specific materials, the diaphragm coated with the electrolyte, and the metal lithium negative electrode plates work together to effectively achieve the purpose of improving energy density.
[0016] Furthermore, lithium tetrafluoroaluminate accounts for 5-20% of the total mass of the electrolyte.
[0017] Another technical solution adopted by the present invention is: the preparation method of the above-mentioned lithium iron phosphate polymer battery comprises the following steps: S1: dissolving lithium iron phosphate and polyvinyl pyrrolidone in ethanol and stirring to obtain a mixture, drying the mixture and then carbonizing and etching in sequence to obtain a positive electrode active material, and preparing a positive electrode sheet using the positive electrode active material; S2: mixing lithium tetrafluoroaluminate and polyethylene oxide by ball milling to obtain an electrolyte, and coating the electrolyte on both sides of the separator; S3: stacking the positive electrode plate, the separator coated with electrolyte and the metal lithium negative electrode plate in sequence to obtain a lithium iron phosphate polymer battery.
[0018] From the above description, it can be seen that the preparation method of the present invention is simple and easy to operate. In the preparation process, an environmentally friendly solvent - ethanol is selected as the solvent. Compared with directly using polyvinyl pyrrolidone as the solvent, in addition to low pollution, it can also speed up the mixing rate and save preparation time cost.
[0019] Furthermore, the stirring time in S1 is 10 to 13 hours.
[0020] Further, the carbonization temperature in S1 is 500-650° C. Preferably, the carbonization temperature in S1 is 560-620° C.
[0021] From the above description, it can be seen that if the carbonization temperature is too low, the graphitization degree of the coated carbon will be insufficient, which will affect the electrochemical properties such as conductivity, and will also prolong the etching time, resulting in low efficiency; if the carbonization temperature is too high, the sample is prone to agglomeration, which will increase the internal resistance of the battery and affect the battery cycle and capacity performance, and will also affect the electrochemical performance and cause the collapse of the structure during subsequent etching. Therefore, the carbonization temperature in S1 is limited to 500~650℃.
[0022] Furthermore, the preparation method of lithium tetrafluoroaluminate is: dissolving aluminum nitrate, ammonium fluoride and lithium nitrate in deionized water, heating and stirring, and drying the heated and stirred mixture and then calcining it to obtain lithium tetrafluoroaluminate.
[0023] Furthermore, the heating and stirring is specifically: stirring at 75-85° C. for 5.5-6.5 hours.
[0024] From the above description, it can be seen that insufficient stirring temperature and time will result in the failure to successfully prepare lithium tetrafluoroaluminate, and too high a temperature may cause decomposition of raw materials and the generation of impurities. Therefore, the heating stirring is limited to: stirring at 75~85°C for 5.5~6.5h.
[0025] Furthermore, the molar ratio of aluminum nitrate, ammonium fluoride and lithium nitrate is 1:3-5:1.
[0026] It can be seen from the above description that if the molar ratio of aluminum nitrate, ammonium fluoride and lithium nitrate is changed, it may cause a difference in their purity and produce more impurities.
[0027] Furthermore, the mass of polyvinyl pyrrolidone is 2-8% of the mass of lithium iron phosphate.
[0028] From the above description, it can be seen that the thickness of the carbon layer is adjusted by controlling the amount of polyvinyl pyrrolidone added. Only when the thickness of the carbon layer is within a specific range can a suitable compaction density of lithium iron phosphate be obtained, thereby improving the energy density.
[0029] Embodiment 1 of the present invention is: a method for preparing a positive electrode sheet of a lithium iron phosphate polymer battery, comprising the following steps: dissolving 100 g of lithium iron phosphate and 2-8 g of polyvinyl pyrrolidone in anhydrous ethanol and stirring for 12 h to obtain a mixture, drying the mixture in an oven and then carbonizing the mixture at 600° C. to form a carbon-encapsulated lithium iron phosphate (see Figure 2), the carbon-wrapped lithium iron phosphate was placed in a CVD tube and a porous carbon structure was etched under ammonia. The ammonia was introduced for 15 min at a rate of 20 mL / min to obtain a positive electrode active material. The prepared carbon-wrapped lithium iron phosphate: PVDF (polyvinylidene fluoride): conductive carbon black were added to N-methylpyrrolidone in a mass ratio of 8:1:1 and stirred to obtain a positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil to obtain a positive electrode sheet.
[0030] Embodiment 2 of the present invention is: a method for preparing a lithium iron phosphate polymer battery, the steps are as follows: S1: The positive electrode sheet of the first embodiment is used.
[0031] S2: Dissolve 89.99 g of aluminum nitrate, 148.15 g of ammonium fluoride and 68.95 g of lithium nitrate in 500 mL of deionized water, and stir in an oil bath at 80°C for 6 h. Dry the heated and stirred mixture in an oven at 70°C. The dried powder is calcined at 400°C for 6 h in an Ar atmosphere to prepare lithium tetrafluoroaluminate.
[0032] S3: 5-20 g of lithium tetrafluoroaluminate and 80-95 g of polyethylene oxide were mixed and placed in a ball mill at 100 rpm for 2 h to obtain an electrolyte.
[0033] S4: Apply the electrolyte to both sides of the separator with a thickness of 30 μm; S5: The metal lithium negative electrode is an ultra-thin lithium strip produced by Zhongneng Lithium. The positive electrode, the diaphragm coated with electrolyte and the metal lithium negative electrode are stacked in sequence, and then spot welded, packaged, baked, left to stand, hot pressed, degassed and divided into different volumes to make samples 1 to 6 finished batteries (see Table 1). The performance of the finished batteries (lithium iron phosphate polymer batteries) is tested, and the test results are shown in Table 2.
[0034] The test method is as follows: The battery internal resistance test uses an internal resistance tester to test the battery cells after capacity division.
[0035] The test method for battery capacity and energy density is as follows: Step 1, charge the formed battery cell 0.5C with constant current and constant voltage to 3.65V, and let it stand for 5 minutes; Step 2, discharge the battery cell 0.5C with constant current to 2.5V, and let it stand for 5 minutes; Step 3, charge the battery cell 5C with constant current and constant voltage to 3.65V, and let it stand for 5 minutes; Step 4, discharge the battery cell 0.5C with constant current to 2.5V, and let it stand for 5 minutes; Step 5, charge the battery cell 5C with constant current and constant voltage to 3.65V, and let it stand for 5 minutes. The test is completed.
[0036] Battery cycle test method: Step 1, the battery cell is initialized to discharge; Step 2, the battery cell is charged at a constant power of 0.5×n×Prcn to a charge termination voltage of 3.65V, and then allowed to stand for 30 minutes; Step 3, the battery cell is discharged at a constant power of 0.5×n´×Prdn' to a discharge termination voltage of 2.5V, and then allowed to stand for 30 minutes; Step 4, cycle steps 2 to 3.
[0037] Table 1
[0038] Table 2
[0039] Comparative Example 1 of the present invention is: a positive electrode sheet and an electrolyte are prepared by a conventional method, and the preparation steps are as follows: S1: Add lithium iron phosphate: PVDF: conductive carbon black in a mass ratio of 8:1:1 to N-methylpyrrolidone and stir to obtain a positive electrode slurry, and apply the positive electrode slurry on a carbon-coated aluminum foil to obtain a positive electrode sheet.
[0040] S2: PEO is used as the electrolyte, and the electrolyte is coated on both sides of the separator with a thickness of 30 μm; S4: The positive electrode plate, the separator coated with electrolyte and the metal lithium negative electrode plate are stacked in sequence, and then spot welded, packaged, baked, left to stand, hot pressed, degassed and divided into different volumes to finally form a finished battery.
[0041] Comparative Example 2 of the present invention is: The difference between Comparative Example 2 and Example 2 is that the mass of polyvinyl pyrrolidone is 10% of the mass of lithium iron phosphate. Comparative Example 3 of the present invention is: The only difference between Comparative Example 3 and Example 2 is that lithium tetrafluoroaluminate accounts for 30% of the total mass of the electrolyte.
[0042] The finished batteries prepared by Sample 2 in Example 2 and Comparative Examples 1 to 3 were subjected to charge and discharge tests. The test results are shown in Figure 3 ,Depend on Figure 3 It can be seen that the capacity of the finished battery prepared by the preparation method of the embodiment is the highest.
[0043] The battery cycle test was carried out on the finished battery prepared by Sample 2 in Example 2 and Comparative Example 1. The test results are shown in Figure 4 ,Depend on Figure 4 As of now, the finished battery prepared by the preparation method of the embodiment is in a stable state, while the comparative example 1 shows a sharp downward trend, and the lithium dendrites generated during the process affect the cycle stability.
[0044] The third embodiment of the present invention is: a lithium iron phosphate polymer battery prepared by the preparation method of the second embodiment.
[0045] Embodiment 4 of the present invention is: a method for preparing a lithium iron phosphate polymer battery, the steps are as follows: S1: 100g lithium iron phosphate and 2g polyvinyl pyrrolidone were dissolved in anhydrous ethanol and stirred for 10h to obtain a mixture, the mixture was placed in an oven for drying and then carbonized at 560°C to form carbon-wrapped lithium iron phosphate, the carbon-wrapped lithium iron phosphate was placed in a CVD tube and a porous carbon structure was etched under ammonia gas, the ammonia gas was introduced for 15min, and the introduction rate was 20mL / min to obtain a positive electrode active material, the prepared carbon-wrapped lithium iron phosphate: PVDF (polyvinylidene fluoride): conductive carbon black was added to N-methylpyrrolidone in a mass ratio of 8:1:1 and stirred to obtain a positive electrode slurry, and the positive electrode slurry was coated on a carbon-coated aluminum foil to obtain a positive electrode sheet.
[0046] S2: 89.99 g of aluminum nitrate, 111.11 g of ammonium fluoride and 68.95 g of lithium nitrate were dissolved in 500 mL of deionized water, and stirred in an oil bath at 75°C for 5.5 h. The heated and stirred mixture was dried in an oven at 70°C. The dried powder was calcined at 400°C for 6 h in an Ar atmosphere to prepare lithium tetrafluoroaluminate.
[0047] S3: 80 g of lithium tetrafluoroaluminate and 20 g of polyethylene oxide were mixed and placed in a ball mill at 100 rpm for 2 h to obtain an electrolyte.
[0048] S4: Apply the electrolyte to both sides of the separator with a thickness of 20 μm; S5: The positive electrode plate, the separator coated with electrolyte and the metal lithium negative electrode plate are stacked in sequence, and then spot welded, packaged, baked, left to stand, hot pressed, degassed and divided into different volumes to finally make a finished battery.
[0049] Embodiment 5 of the present invention is: a method for preparing a lithium iron phosphate polymer battery, the steps are as follows: S1: 100g lithium iron phosphate and 8g polyvinyl pyrrolidone were dissolved in anhydrous ethanol and stirred for 13h to obtain a mixture, the mixture was placed in an oven for drying and then carbonized at 620°C to form carbon-wrapped lithium iron phosphate, the carbon-wrapped lithium iron phosphate was placed in a CVD tube and a porous carbon structure was etched under ammonia gas, the ammonia gas was introduced for 15min, and the introduction rate was 20mL / min to obtain a positive electrode active material, the prepared carbon-wrapped lithium iron phosphate: PVDF (polyvinylidene fluoride): conductive carbon black was added to N-methylpyrrolidone in a mass ratio of 8:1:1 and stirred to obtain a positive electrode slurry, and the positive electrode slurry was coated on a carbon-coated aluminum foil to obtain a positive electrode sheet.
[0050] S2: 89.99 g of aluminum nitrate, 185.18 g of ammonium fluoride and 68.95 g of lithium nitrate were dissolved in 500 mL of deionized water, and stirred in an oil bath at 85°C for 6.5 h. The heated and stirred mixture was dried in an oven at 70°C. The dried powder was calcined at 400°C for 6 h in an Ar atmosphere to prepare lithium tetrafluoroaluminate.
[0051] S3: 95 g of polyethylene oxide and 5 g of lithium tetrafluoroaluminate were mixed and placed in a ball mill at 100 rpm for 2 h to obtain an electrolyte.
[0052] S4: Apply the electrolyte to both sides of the separator with a thickness of 40 μm; S5: The positive electrode plate, the separator coated with electrolyte and the metal lithium negative electrode plate are stacked in sequence, and then spot welded, packaged, baked, left to stand, hot pressed, degassed and divided into different volumes to finally make a finished battery.
[0053] In summary, the lithium iron phosphate polymer battery provided by the present invention can effectively achieve the purpose of improving energy density through the joint action of the positive electrode plate of specific material, the separator coated with electrolyte and the metal lithium negative electrode plate. The battery and its preparation method have the following advantages: 1. Choose metallic lithium as the negative electrode, which is lightweight and has high theoretical capacity.
[0054] 2. Lithium tetrafluoroaluminate and polyethylene oxide are used as electrolytes. When they come into contact with the metallic lithium negative electrode, lithium tetrafluoroaluminate will construct a three-dimensional structure with the metallic lithium and grow an Al-Li alloy with good conductivity, which can inhibit lithium deposition and the formation of lithium dendrites. At the same time, a stable SEI film will be formed to reduce the formation of lithium dendrites and improve energy density.
[0055] 3. Using porous carbon-wrapped lithium iron phosphate as the positive electrode can effectively avoid interfacial reactions, reduce the internal resistance of the system, reduce the polarization caused by the internal resistance, increase its voltage platform and thus enhance the energy density, and also reduce the side effects of polyethylene oxide oxidative decomposition caused by interfacial reactions.
[0056] 4. The carbon in the positive electrode has a porous structure, which can increase the reaction channels of lithium ions and enhance energy density.
[0057] 5. The preparation method of the battery is simple and easy to operate. In the preparation process, an environmentally friendly solvent, ethanol, is selected as the solvent, which can accelerate the mixing rate.
[0058] 6. When preparing the battery, the thickness of the carbon layer is adjusted by controlling the amount of polyvinyl pyrrolidone added to obtain a suitable compaction density of lithium iron phosphate, thereby improving the energy density.
[0059] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a lithium iron phosphate polymer battery, characterized in that: The invention comprises the steps of preparing a positive electrode sheet, wherein the preparation method of the positive electrode sheet comprises: dissolving lithium iron phosphate and polyvinyl pyrrolidone in ethanol and stirring, and then sequentially drying, carbonizing and etching with ammonia to obtain porous carbon-wrapped lithium iron phosphate; preparing the positive electrode sheet using the porous carbon-wrapped lithium iron phosphate as the positive electrode active material; the mass of the polyvinyl pyrrolidone is 2-8% of the mass of the lithium iron phosphate.
2. The method for preparing a lithium iron phosphate polymer battery according to claim 1, characterized in that: The carbonization temperature is 560-620°C.
3. The method for preparing a lithium iron phosphate polymer battery according to claim 1, characterized in that: During the ammonia etching, the ammonia gas was introduced for 15 min at a rate of 20 mL / min.
4. The method for preparing a lithium iron phosphate polymer battery according to claim 1, characterized in that: The method also includes the step of preparing the electrolyte: mixing lithium tetrafluoroaluminate and polyethylene oxide and ball-milling to obtain the electrolyte.
5. The method for preparing a lithium iron phosphate polymer battery according to claim 4, characterized in that: The preparation method of lithium tetrafluoroaluminate is as follows: aluminum nitrate, ammonium fluoride and lithium nitrate are dissolved in deionized water, heated and stirred, and the heated and stirred mixture is dried and calcined to obtain lithium tetrafluoroaluminate.
6. The method for preparing a lithium iron phosphate polymer battery according to claim 5, characterized in that: The stirring temperature of the heating stirring is 75-85° C., and the stirring time is 5.5-6.5 h.
7. The method for preparing a lithium iron phosphate polymer battery according to claim 5, characterized in that: The molar ratio of the aluminum nitrate, ammonium fluoride and lithium nitrate is 1:3-5:
1.
8. The method for preparing a lithium iron phosphate polymer battery according to claim 4, characterized in that: The lithium tetrafluoroaluminate accounts for 5-20% of the total mass of the electrolyte.
9. The method for preparing a lithium iron phosphate polymer battery according to claim 4, characterized in that: The method also includes the steps of coating the electrolyte on both sides of the diaphragm, and then sequentially stacking the positive electrode sheet, the diaphragm coated with the electrolyte, and the metal lithium negative electrode sheet.
10. A lithium iron phosphate polymer battery prepared by the method for preparing a lithium iron phosphate polymer battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of carbon-coated LiFEPO4 / CNTs composite positive electrode material for lithium ion battery
CN107732174A
Polymer interface modified inorganic solid electrolyte as well as preparation method and application thereof
CN116565301A
Lithium iron phosphate system lithium ion battery and preparation method thereof
CN107046131A
Lithium iron phosphate composite electrode with metal oxide coating layer on surface
CN107634177A
Lithium iron phosphate positive electrode material of high compaction density and positive pole piece
CN108878797A